Is the Contracts Act 1950 (Malaysia) suitable on the internet : a critical evaluation - Md. Abdul Jalil (Fakulti Undang - Undang, 2003)

(untitled)
The Contracts Act 1950 (Malaysia) is an old statute which basically provides postal rule to govern the formation of a contact made by sending letters through post office. It is silent about the emerging new issues on the Internet contracts. When technology advances the law lags behind. So, the old laws are usually modified to adapt to the new environment. At present time electronic commerce is expanding very rapidly everywhere on the globe including Malaysia. Millions of customers are buying goods and services on the Internet. As a result volumes of contracts are made on the Internet. Some of the disputes which are now arising out of the online contracts are new and the existing contract laws in Malaysia are unable to solve those problems, such as the validity of using data message to form a contract, the requirement of writing and signature on paper for certain contracts, time of dispatch and receipt of data message, time when an electronic acceptance is effective, whether postal rule or receipt rule will be applicable on the Internet contract and so forth. This article analysis the above issues with reference to the Malaysian contract law, UNCITRAL Model Law on Electronic Commerce and Electronic Transactions Act 2000 (Singapore)